Selection of Large-scale Nuclear Power Plant Based on Economic and Reliability Aspects in Indonesian Power System - Budi, Rizki Firmansyah Setya; Birmano, Moch. Djoko; Amitayani, Elok Satiti (International Journal of Energy Economics and Policy, 2021)
Choosing the Indonesia's power systems that are suitable with the large-scale nuclear power plant (NPP) and the NPP's vendor country are crucial problems faced by Indonesian government. Therefore, this research analyzes the NPP impact on the power system reliability to choose the suitable power systems and the NPP economics of each possible vendor country to choose the optimal vendor that provides minimize cost. This research uses two electricity price scenarios: electricity production cost (scenario 1) and adjustment tariff (scenario 2). The results show that only Sumatra and Java-Bali system can be connected with the NPP. For both of these systems, Japanese NPP is not economical to be developed because it provides a levelized unit electricity cost (LUEC) of 0.116 USD/kWh, which is higher than the electricity prices. Meanwhile, Chinese and South Korean NPP is economical to be developed in both systems. For the Java-Bali system, Chinese NPP is the best choice in scenario 1 with a LUEC of 0.036 USD/kWh. In scenario 2, South Korean NPP that has a LUEC of 0.058 USD/kWh becomes the best choice because it has better public perception than Chinese. For the Sumatra system, South Korean NPP is the best choice in both scenarios. Keywords: Large-scale NPP selection, Indonesia power system, Reliability, Minimize cost, Electricity price JEL Classifications: D21, D22, E39 DOI: https://doi.org/10.32479/ijeep.11107